Autonomia universitária: entre garantias legais e ameaças políticas - Santi, Rafael Porto (Universidade Federal de São Carlos, 2025)
The 1988 Federal Constitution, in articles 206 and 207, guarantees public universities full academic, scientific, administrative and financial management autonomy. The autonomous university represents one of the pillars of the Democratic State of Law, given that it allows the production and dissemination of knowledge and the pluralism of ideas. In this context, important questions arise: have the actions of the Presidents of the Republic weakened university autonomy? Do the actions of the federal government, especially between 2019 and 2022, constitute political intervention in universities? Is university autonomy consolidated at its foundations? This study aims to investigate these questions based on three main axes: (i) the analysis of university autonomy as a constitutional principle and its scope; (ii) the understanding of the relationship between university autonomy and the development of democracy; and (iii) the evaluation of the performance of the federal Executive Branch in relation to public universities, with special attention to the appointment of rectors of federal higher education institutions. With a qualitative approach, the documentary research establishes a comparison between the appointments made by the President of the Republic between the periods of 2018 to 2022 and 2010 to 2014. It specifically analyzes whether the appointments were made based on the list of three candidates sent by the universities to the Ministry of Education, comparing the presidential acts with the manifestations of the university communities. The intention is to highlight possible tensions between the acts of the Executive and the constitutional principles that guarantee university autonomy in Brazil.
University autonomy: between legal guarantees and political threats
Keywords: Autonomia Universitária; Nomeação de Reitores; Políticas Públicas; Democracia; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; 16. Paz, Justiça e Instituições Eficazes